E-Module Development with Kvisoft Flipbook Maker Application on Economics Material to Improve Students' Critical Thinking Abilities - Mila Suci Windiarti; Kiromim Baroroh (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This study aims to determine (1) the design of an e-module model with the Kvisoft Flipbook Maker application in economics learning to improve participants' critical thinking skills. Educate, (2) the feasibility of e-modules with the Kvisoft flipbook maker application in economic learning to improve participants' critical thinking skills. learners, (3) students' learning responses to electronic module (e-module) with the Kvisoft flipbook maker application in economics learning for participants Educate, (4) how effective is the use of e-modules with the Kvisoft Flipbook Maker application for critical thinking skills of students in learning .This research is a development research with R&D model. The research sample is SMPN 28 Purworejo class VIII students totaling 92 divided into 2 groups, namely the experimental group, and the control group , the control class uses printed e-modules . Data analysis techniques use normality tests, homogeneity, hypothesis testing, further testing, and effect size.The research results show (1) The experimental class showed that the gain in critical thinking skills of students in the experimental class was 0.8, which means that the gain value in the experimental class was in the range of values (<g>) > 0.7, which is in the high category, in the control class the gain value 0.5 which means the gain in the first and second control classes is in the range of 0.7 ≥ (<g>) 0.3 is in the medium category, (2) the e-module suitability from the assessment of material experts is 5.47 and 5.55, media experts 4.46 with very good and good categories, (3) the student response is good as seen from the results of the content suitability of 4.27, language 8.41, usefulness 8.68, and graphics 8.57 are at a value above 4, (4) the results of the effect size analysis with the Interpretation Effect Size category show that using the Kvisoft Flipbook Maker e-module is effective in increasing critical thinking skills by 70.8 %.